TB DOTS STRATEGY IN DISTRICT RAWALPINDI: RESULTS AND LESSONS - Iram, Samia; Ali, Shafqut; Khan, Shahbaz Ali; Abbasi, Munir A; Anwar, Syed Abbas; Fatima, Fozia (Journal of Ayub Medical College Abbottabad, 2011)
Background: Tuberculosis (TB) is one of the most ancient diseases of mankind. Despite newer modalities for diagnosis and treatment, unfortunately, people are still suffering, and TB is among the top 10 killer infectious diseases in the world. TB is a devastating disease due to its rapid transmission and high rate of mortality causing around 1.8 million deaths annually. This study was conducted to evaluate the effectiveness of the Directly Observed Therapy Short-course (DOTS) in the target population. Methods: Two Tehsils of District Rawalpindi were selected for the study. All patients under TB treatment attending Basic Health Units (BHUs) and Rural Health Centres (RHCs) were included in the study. The patients with extra pulmonary TB and children under five years of age were excluded from the study. All patients were contacted individually and asked about the DOTS program activity using a preformed questionnaire that mainly contained questions regarding knowledge of the patients about their disease and the role of health facility in treating and following the disease. Results: Out of the 224 patients who were included in the study, 87 (38.8%) were male, and 137 (61.2%) were female. Majority (48.8%) of the patients was in age group of 21-40 years and 62.5% patients had positive family history of TB. Among the patients, 51.8% were illiterate, 31.7% had studied till primary level, and only 16.5% had the educational qualification of Matric or above. In our study 69.2% of patients themselves or through their relatives reported to the health facilities to get treatment, while the rest were picked by community health workers, 62.9% were diagnosed by the public hospitals, 23.2% were diagnosed by general practitioners and 12.9% by the federal public hospitals. In our study 69.6% of the patients were not observed at all or were observed by the family members. Conclusion: TB is mainly a disease of the poor and illiterate people. Despite many achievements a bulk of patients are not picked by the community health providers nor are they properly observed. We need to improve the current working of the DOTS personnel. General practitioners are playing a big role in diagnosing the disease, so they need to be integrated in the DOTS to effectively diagnose and control TB. Keywords: Tuberculosis, DOTS, Practitioners, Health Care Providers, Primary Health Care, Pakistan